Reinforced asphalt overlays for pavements - Sanders, Paul John (2001)
The maintenance of road pavements in England has become a costly necessity, due largely to the large volume of commercial vehicles using the roads which cause pavements to deteriorate quickly, and makes their repair more difficult to carry out. These roadworks incur not only direct works costs, but also indirect costs from factors such as congestion, motor accidents and pollution. There is obviously a need for cost-effective maintenance that minimises the occurrence and duration of these disruptions. To strengthen pavements bituminous overlays are often used, but may crack prematurely when placed over a layer with discontinuities such as cracks or joints, or deform excessively under wheel loading. The problem of 'reflective cracking' is widespread and reduces the life of maintenance treatments considerably. To increase the time before cracking appears on the surface of a pavement, a (more expensive) thicker overlay may be used, but this can lead to problems with property thresholds and bridge clearance. One possible option of reducing the thickness of overlays by making them more resistant against cracking and deformation, is to place a layer-of reinforcement within or at the bottom of the overlay. Although this approach has been used occasionally to reinforce overlays, over 40 years or so, it is not favoured with many road authorities, as the results of these treatments are difficult to anticipate, and may not be cost effective.